Heparanase contributes to pancreatic carcinoma progression through insulin-dependent glucose uptake - Abecassis, Alexia; Hermano, Esther; Yifrach, Adi; Popovtzer, Aron; Meirovitz, Amichay; Elkin, Michael (Frontiers in Cell and Developmental Biology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive tumor, which is highly resistant to existing therapies and characterized by one of the lowest survival rates known for solid cancers. Among the reasons for this poor prognosis are unique pathophysiological features of PDAC, such as dense extracellular matrix [ECM] creating barriers to drug delivery, as well as systemically-deregulated glucose metabolism manifested by diabetic conditions (i.e., hyperinsulinemia/hyperglycemia) occurring in the majority of PDAC patients. Moreover, in addition to systemically deregulated glucose homeostasis, intracellular metabolic pathways in PDAC are rewired toward increased glucose uptake/anabolic metabolism by the tumor cells. While the role of oncogene-driven programs in governing these processes is actively studied, mechanisms linking metabolic dysregulation and ECM enzymatic remodeling to PDAC progression/therapy resistance are less appreciated. The aim of the current study was to investigate the action of heparanase (the predominant mammalian enzyme that degrades heparan sulfate glycosaminoglycan in the ECM), as a molecular link between the diabetic state and the intracellular metabolic rewiring in PDAC pathogenesis. Here we show that in PDAC elevated levels of heparanase, coupled with diabetic conditions typical for PDAC patients, promote growth and chemotherapy resistance of pancreatic carcinoma by favoring insulin receptor signaling and GLUT4-mediated glucose uptake into tumor cells. Collectively, our findings underscore previously unknown mechanism through which heparanase acts at the interface of systemic and intracellular metabolic alterations in PDAC and attest the enzyme as an important and potentially modifiable contributor to the chemo-resistance of pancreatic tumors.